IN THE BEGINNING - Guthrie, W. K. C. (William Keith Chambers), 1906-1981. Link ([S.l.])
1 online resource
Keywords: In the Beginning (1957) represents a series of lectures given by the author at Cornell University, examining the views of the Ancient Greeks on the central foundation myths of their civilisation. From stories of mother earth to later philosophical and scientific approaches, their thoughts are analysed in this key reference work.